2019
DOI: 10.3390/polym11122059
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Preparation Method and the Dispersion and Aspect Ratio of CNTs on the Mechanical and Electrical Properties of Bio-Based Polyamide-4,10/CNT Nanocomposites

Abstract: Bio-based polymeric nanocomposites (NCs) with enhanced electrical conductivity and rigidity were obtained by adding multi-walled carbon nanotubes (CNTs) to a commercial bio-based polyamide 4,10 (PA410). Two different types of commercial CNTs (Cheap Tubes and Nanocyl NC7000 TM ) and two different preparation methods (using CNTs in powder form and a PA6-based masterbatch, respectively) were used to obtain melt-mixed PA410/CNT NCs. The effect of the preparation method as well as the degree of dispersion and aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 41 publications
3
34
0
Order By: Relevance
“…(4)) as a function of (a) "R" and "l" and (b) "t" and "u" factors. Figure 3 exhibits the effects of different parameters on "fiu" term as the fraction of percolated filler above percolation threshold using Equation (6). Figure 3a indicates that the least "fiu" as about 0.05 is obtained at R = 50 nm and l = 3 μm, while the smallest level of "R" and l > 10 μm significantly improve the level of "fiu" to 0.28.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(4)) as a function of (a) "R" and "l" and (b) "t" and "u" factors. Figure 3 exhibits the effects of different parameters on "fiu" term as the fraction of percolated filler above percolation threshold using Equation (6). Figure 3a indicates that the least "fiu" as about 0.05 is obtained at R = 50 nm and l = 3 μm, while the smallest level of "R" and l > 10 μm significantly improve the level of "fiu" to 0.28.…”
Section: Resultsmentioning
confidence: 99%
“…Polymers 2020, 12, 404 7 of 13 Figure 3. The variations of "fiu" term at different levels of (a) "R" and "l" and (b) "t" and "u" parameters according to Equation (6). Figure 4 illustrates the influences of "R" and "l" parameters on the electrical conductivity of PCNT predicted by the conventional and developed models in Equations (9) and (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbon nanotubes (CNT) as ideal nanoparticles can add high stiffness and good electrical conductivity to polymer matrices. Additionally, the nanoscale diameter and large aspect ratio of CNT significantly improve the general properties of polymer CNT nanocomposites (PCNT) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The van der Waals attraction between nanotubes leads the aggregation/agglomeration in the nanocomposites, which reduces the filler surface expanse and interrupts the networking level [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes (CNT) have involved significant interest in nanocomposites due to amazing mechanical behavior and good electrical conductivity, as well as nanometer size and high aspect ratio [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. It was reported that only a low content of CNT is enough to prepare a nanocomposite with significant mechanical and conductivity properties.…”
Section: Introductionmentioning
confidence: 99%